Role of Teachers and Parents in Realizing Character Education in the Digital Era - Ritonga, Apri Wardana (Indonesian Values and Character Education Journal, 2022)
The digital era in fact still gives teachers and parents worries with various content that leads to "negative" changes in student attitude. In addition, teachers and parents still throw responsibilities at each other when students' attitudes deviate from character values. This study aims to explore the role of teachers and parents in realizing a character generation in the midst of digital development. This study adopts a qualitative descriptive approach with the library research method. Data is collected from primary and secondary sources such as research reports in international and national journals, proceedings articles, and books. The data analysis technique uses descriptive content analysis by selecting, processing, and describing the data findings into research results. The results of this study indicate that parents and teachers have the same role and have a great influence in implementing character education in the digital era, through programs developed in schools and monitoring, mentoring, and learning activities from parents to children at home. The findings of this study describe that teachers and parents are special creatures that Allah sent to mediate the realization a generation of characters according to Islamic guidance.